Un infierno catalán. Apuntes para una bibliografía de publicaciones eróticas catalanas clandestinas (siglo XIX - primer tercio del siglo XX). - GUEREÑA, JEAN-LOUIS (Scripta, 2014)
This article collects a good number of Catalan publications with a erotic topic that came out clandestinely during the 19th and early 20th centuries.